2007
DOI: 10.1002/jbm.a.31562
|View full text |Cite
|
Sign up to set email alerts
|

T cell subset distributions following primary and secondary implantation at subcutaneous biomaterial implant sites

Abstract: Synthetic biomaterials are considered to be nonimmunogenic. Therefore, the role that adaptive immunity may play in the host response to implanted synthetic biomaterials has not been extensively studied. Cardinal features of adaptive immunity include specificity and T cell responses, which are greater and more effective with upregulation of activation receptors upon rechallenge. We compared the primary and secondary in vivo host response to three synthetic biomaterials: Elasthane 80A, silicone rubber, and polye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…Macrophages and other phagocytic cells were found to play a major role within these reactions [4] while T cells are also involved [5]. However, more studies are needed to elucidate their exact role [6,7].…”
Section: Introductionmentioning
confidence: 98%
“…Macrophages and other phagocytic cells were found to play a major role within these reactions [4] while T cells are also involved [5]. However, more studies are needed to elucidate their exact role [6,7].…”
Section: Introductionmentioning
confidence: 98%
“…In the context of this response, macrophages and other phagocytic cells play a central role [10]. Furthermore, T-cells have been implicated in the host reaction after implantation of biomaterials [11], although their exact role remains unknown [12,13]. In the context of the present implant improvement approach, study of inflammatory response is of special importance, since the coated titanium surface will be the cell contacting material.…”
Section: Introductionmentioning
confidence: 98%
“…These interactions are also dependent on biomaterial surface chemistry (MacEwan et al, 2005) and lead to biomaterial-dependent cytokine production (Chang et al, 2008a) and both direct and indirect interactions with lymphocytes enhance macrophage/FBGC biomaterial-dependent activation for cytokine production (Chang et al, 2008b; Chang et al, 2009). In vivo in the context of the foreign body reaction, we have demonstrated that secondary responses to biomaterial implantation are characterized by recruitment of both T lymphocytes and phagocytic cells (Rodriguez et al, 2008). …”
Section: Introductionmentioning
confidence: 99%